Murine esophagus expresses glial‐derived central nervous system antigens - Kapitza, Christopher; Chunder, Rittika; Scheller, Anja; Given, Katherine S.; Macklin, Wendy B.; Enders, Michael; Kürten, Stefanie; Neuhuber, Winfried; Wörl, Jürgen (International Journal of Molecular Sciences, 2021)
Multiple sclerosis (MS) has been considered to specifically affect the central nervous system (CNS) for a long time. As autonomic dysfunction including dysphagia can occur as accompanying phenomena in patients, the enteric nervous system has been attracting increasing attention over the past years. The aim of this study was to identify glial and myelin markers as potential target structures for autoimmune processes in the esophagus. RT‐PCR analysis revealed glial fibrillary acidic protein (GFAP), proteolipid protein (PLP), and myelin basic protein (MBP) expression, but an absence of myelin oligodendrocyte glycoprotein (MOG) in the murine esophagus. Selected immunohistochemistry for GFAP, PLP, and MBP including transgenic mice with cell‐type specific expression of PLP and GFAP supported these results by detection of (1) GFAP, PLP, and MBP in Schwann cells in skeletal muscle and esophagus; (2) GFAP, PLP, but no MBP in perisynaptic Schwann cells of skeletal and esophageal motor endplates; (3) GFAP and PLP, but no MBP in glial cells surrounding esophageal myenteric neurons; and (4) PLP, but no GFAP and MBP in enteric glial cells forming a network in the esophagus. Our results pave the way for further investigations regarding the involvement of esophageal glial cells in the pathogenesis of dysphagia in MS.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Autoantibodies; Dysphagia; Enteric glia; Enteric nervous system; Esophagus; Glial fibrillary acidic protein; Motor endplate; Multiple sclerosis; Myelin basic protein; Proteolipid protein